Assistance For MSMES in The Adoption of Digital Marketing of Local Food Products - Sutarni, Sutarni; Berliana, Dayang; Saputra, Kurniawan; Fitriani, Fitriani (Unram Journal of Community Service, 2024)
One of the agro-industry players in processed food products in Punggur District, Central Lampung Regency, Lampung Province, is KWT Canala. KWT in Punggur Regency merged into an organization called the KWT forum of Punggur Regency. The application of digital marketing technology in KWT in Punggur District, Central Lampung Regency is;  The application of the internet is still very limited, this is due to the low skills of internet applications that can be used in business. The low use of digital media in business is caused by incompetent expertise in using the internet, social media, marketplaces, and product promotion.  Therefore, it is necessary to provide assistance to KWT members in implementing digital marketing so that sales volume increases. This program aims to provide assistance to MSMEs in Punggur Regency related to the manufacture of attractive labels and packaging that are able to compete in the market as well as the application of digital marketing in improving the performance of local food product businesses so that it can increase KWT's sales volume and revenue. The methods used are lectures, discussions and demonstrations through pre-activity activities (permit management, consolidation), exercises and demonstrations, development and evaluation of online stores (initial evaluation, process evaluation and evaluation of results or sustainability impacts). The result of this program is to improve the knowledge and skills of MSME managers in Punggur District about making labels, packaging and the use of digital marketing for products to be produced.